2021
DOI: 10.1007/s42991-020-00099-7
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of genetic isolation of the three lineages of the narrow-headed vole Lasiopodomys gregalis (Cricetidae, Rodentia) in a mosaic steppe landscape of South Siberia

Abstract: Geographic isolation is among the most important factors initiating speciation in mammals. The narrow-headed vole Lasiopodomys gregalis is a widely distributed species in steppe habitats of South Siberia that are highly fragmented by mountain ranges. There are three major mostly allopatric mitochondrial lineages of L. gregalis described throughout the distribution range that most plausibly split in the Middle Pleistocene. This study applies the analysis of five microsatellite loci and species distribution mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The results of experimental breeding showed the presence of posterity in all combinations of A, B, and C L. gregalis lineages; however, it was shown that not every reciprocal combination had posterity that was numerous and viable [9,10]. Using a microsatellite loci analysis [11] we found traces of hybridisation in the two most phylogenetically close lineages, B and C, which, according to our estimates [7], separated about 250 thousand years ago. Despite the absence of continuous geographical barriers in nature between the lineage distribution ranges, we did not find any traces of hybridization from lineage A with lineages B and C, separation from which probably occurred about 400 thousand years ago.…”
Section: Traces Of Molecular Differentiation At the Early Stages Of S...mentioning
confidence: 67%
See 1 more Smart Citation
“…The results of experimental breeding showed the presence of posterity in all combinations of A, B, and C L. gregalis lineages; however, it was shown that not every reciprocal combination had posterity that was numerous and viable [9,10]. Using a microsatellite loci analysis [11] we found traces of hybridisation in the two most phylogenetically close lineages, B and C, which, according to our estimates [7], separated about 250 thousand years ago. Despite the absence of continuous geographical barriers in nature between the lineage distribution ranges, we did not find any traces of hybridization from lineage A with lineages B and C, separation from which probably occurred about 400 thousand years ago.…”
Section: Traces Of Molecular Differentiation At the Early Stages Of S...mentioning
confidence: 67%
“…were well isolated from each other genetically (gene flow between them was strongly limited and traces of hybridisation were found in only the contact zone of lineages B and C). A species distribution modeling analysis predicted the presence of barriers between the lineages that correspond to landscape heterogeneity and only a small number of potential contact zones [11]. These results suggested that these three genetic lineages of L. gregalis s. str.…”
Section: Introductionmentioning
confidence: 91%
“…1, sampling site 4). It is di cult to guess the reasons for this nding, but it is curious that an individual with Bs was collected in the area of the probable separation of the three genetic lineages A, B and C. Perhaps an analysis of representatives of lineage A from the eastern part of the Tuva Basin and Southern slopes of the Western Tannu-Ola Range (Petrova et al, 2021) will resolve this question.…”
Section: Polymorphism Of Supernumerary Chromosomes the Evolutionary C...mentioning
confidence: 99%
“…1). Despite the presence of several potential contact zones in the Altai-Sayan Region, lineages A, B and C were reported to be well isolated from each other genetically, which allows us to recognise them as separate taxa (Petrova et al, 2021). The mechanisms of their isolation are not yet clear, because experimental breeding did not reveal clear signs of reproductive isolation between them (Petrova et al, 2016).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation